Donors, Noncommunicable Diseases, and Universal Health Coverage to High-quality Healthcare: An Opportunity for Action on Global Functions for Health - Lyndsay S. Baines; David J. Kerr (Springer, 2018)
Hatefi and Allen [1] point the complex global health landscape confronting donors, consisting of multiple chronic diseases across a broad epidemiological cohort, in both low- and middle-income countries. The authors contemplate donor choices for investment from the bilateral perspective of universal health coverage (UHC) versus diseases caused by high-risk lifestyle choices.